High mortalities among one-humped camels (Camelus dromedarius) due to salinomycin poisoning in the Kingdom of Saudi Arabia - Abu-Samra, Mukhtar Taha; Shuaib, Yassir Adam (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: The objective of this study was to investigate the cause of death of large number of camels during an outbreak in Saudi Arabia. Material and methods: History was taken from the camel owners and breeders. Besides, clinical and post-mortem (PM) examinations were conducted. In this study, ten locations were surveyed and all camels were examined. Wheat bran was suspected as the source of the havoc. For establishing this assumption, a feeding trial was conducted with three camels, six mice, one rabbit and four of each chickens and ducklings using the incriminated wheat bran. Samples were collected from the suspicious wheat bran and the afflected animals, and were sent to international reference laboratories for diagnosis. The clinical signs elicited by the feeding trial were compared with the signs recorded in the outbreak. Results: The body temperature of the affected camels ranged from 36.4°C to 41.9°C. The clinical signs included hyper-excitability, muscle tremors, in-coordination of the hind quarters, sternal or lateral recumbence, inability to stand, and death. PM examination revealed no remarkable pathological changes in internal organs but the rumens were full of gases, and showed hyperemia and petechial hemorrhages. Within a period of twelve days from the onset of the crisis, 2,800 of the affected camels died. The clinical signs showed by the two camels in the feeding trial were similar to those observed in field outbreak. The tentative diagnosis of toxicosis, which was made based on the clinical signs was confirmed by the reference laboratories. Salinomycin (300 to 400 mg/Kg feed), Aluminium (230 ppm), Aspergillus clavatus and A. flavus were detected in the incriminated wheat bran. Conclusion: Salinomycin causes heavy mortalities in one-humped camels in the affected areas. Owners and breeders are adviced to avoid feeding low quality feed to their camels. http://doi.org/10.5455/javar.2017.d206 XML PubReader